STUDI KARAKTERISTIK FISIK WILAYAH BANJIR ROB DI KOTA DUMAI TAHUN 2020 - Agung Agung Prayitno (JURNAL BUANA, 2022)
ABSTRACT The city of Dumai has a high intensity of rain followed by high tides that cause tidal flooding on the coast of Dumai. Based on this, a study was conducted to determine the characteristics of the tidal flood area based on the tidal flood vulnerability variable in Dumai City, the distribution of tidal flood vulnerability in Dumai City, and the spatial distribution of the population in the tidal flood prone area in Dumai City. This type of research is quantitative using the Kingma method. Based on the results of the study, it was found that there are many settlements on the coastline and river bodies, and there are 5 sub-districts that are prone to flooding, namely Medang Kampai District 574 Ha, Sungai Sembilan District 2,022 Ha, Dumai City District 68 Ha, Dumai Timur District 186 Ha, Dumai Barat District 261 Ha. The number of people affected by tidal flooding in Dumai City is in Dumai City District 2,920 people, West Dumai District 2,688 people, Medang Kampai District 2,115 people, Dumai Timur District 1,500 people, and Sungai Sembilan District 595 people. Keywords-Kingma, ROBFlood, Dumai City.